Application of commercial seaweed extract-based biostimulants to enhance adventitious root formation in ornamental cutting propagation protocols: a review - Loconsole, Danilo; Scaltrito, Eugenio; Sdao, Anna Elisa; Cristiano, Giuseppe; De Lucia, Barbara (Frontiers in Horticulture, 2024)
Despite significant advancements in stem-cutting propagation, insufficient rooting efficiency remains an economic burden for the ornamental nursery industry. IBA and NAA play a critical role in generating adventitious roots (AR) when applied exogenously. In sustainable agriculture, the substitution of chemical inputs, with alternative natural eco-friendly products presents a key challenge. Biostimulants can form part of a solution to mitigate such risks deriving from the use of agrochemicals, they are generally considered to be non-toxic, non-polluting, biodegradable, and non-hazardous. The current knowledge of the use of commercial seaweed extract (SE) products applied to ornamental cutting propagation has not been summarized until now. Therefore, we conducted a systematic review, and we hypothesized that SE-based biostimulant application to ornamental stem cuttings improves AR formation in terms of rooting percentage, root number, and architecture. Moreover, they increase the overall quality of a rooted cutting as dry biomass and organic compound content. The authors chose SE-based biostimulants because they have been proven to have an extremely low carbon footprint; moreover, they are expected to account for more than 33% of the global market for biostimulants and reached a value of 894 million Euros by 2022. This review focuses on (i) SE-based biostimulants, in particular, brown algae; (ii) technical information on five commercial products: Goteo®, Kelpak®, AlgaminoPlant, Bio Rhizotonic, Actiwawe and others, less known, also used as phytoregulators substitutes; (iii) applied protocols, describing dose, application method, number of treatments, cutting type; (iv) effects of applied protocols on rooting rate, root architecture and overall rooted cutting quality. Outcomes show that findings vary based on crops, cuttings, location, raw materials, composition, dose, application number and procedures, and growth environment.